Anggaran Partisipatif, Senjangan Anggaran, Kinerja Aparatur Pemerintah dan Tata Kelola Pemerintahan (Studi pada Pemerintah Daerah Kabupaten Malang) - Sylvia Puspitasari, Devy; Djamruhi, Ali; Subekti, Imam (Jurnal Ilmiah Administrasi Publik, 2017)
This study aims to examine the influence of partisipative budgeting on budgetary slack, the influence of partisipative budgeting and government apparatus performance are moderated by government governance in Regional Government of Malang. The results showed the greater level of budgetary participation, it will decrease budgetary slack, but government governance is not moderate the influence of partisipative budgeting on budgetary slack. The results also showed participative budgeting will increase government apparatus performance, and government governance strengthen the influence partisipative budgeting on government apparatus performance.